Öffentliche Räume unter Schrumpfungsbedingungen. - Overhageböck, Nina (My University, 2009)
Der Arbeit liegt die Frage zugrunde, welche Wirkungen die Schrumpfung einer Stadt, d.h. deren Bevölkerungsrückgang, wirtschaftlicher Niedergang sowie die desolaten Kommunalfinanzen auf die öffentlichen Räume haben und wie sich der Umgang der kommunalen Stadtplanung mit diesem zentralen Handlungsfeld unter Schrumpfungsbedingungen gestaltet. Ziel ist es, ein bislang wenig erschlossenes Forschungsfeld durch eine Sekundäranalyse des vorhandenen Wissensbestandes sowie eine empirische Analyse mittels Experteninterviews zu erschließen. Die Ergebnisse der Untersuchungen zeigen, dass Schrumpfung sowohl eine Vielzahl räumlicher Veränderungen als auch einen Wandel im Handeln kommunaler Stadtplaner im zentralen Handlungsfeld des öffentlichen Raumes erzeugt. Zu diesen Auswirkungen zählen: ein quantitatives Wachstum öffentlicher Räume, eine geringere Nutzungsdichte, eine veränderte Nutzerstruktur, eine nachlassende soziale Kontrolle, eine strategische Schwerpunktsetzung in Bezug auf Grün- und Freiflächen sowie ein umfassendes Management öffentlicher Räume durch die kommunalen Akteure. Unter Schrumpfungsbedingungen setzt sich also ein bereits in anderen städtischen Kontexten beobachteter Wandel öffentlicher Räume fort. Er erfasst insbesondere die traditionellen Kennzeichen und die Position kommunaler Akteure in der Weise, dass einerseits die stadtsoziologischen Schlüsselbegriffe zur Beschreibung, Erfassung und Erklärung öffentlicher Räume unter Schrumpfungsbedingungen nicht mehr passend erscheinen. Andererseits wird die Produktion des städtischen Außenraumes da an seine Grenzen stoßen, wo vor allem die Kooperationsbereitschaft und Mitwirkung der Bürger und Flächeneigentümer sowie externe Fördermittel nicht mehr passgenau ineinandergreifen.

This thesis explores the question to which extend city shrinkage, i.e. decrease of population, economic decline and severe constraints of municipal finances, has got an impact on public space and how local planning authorities provide governance for public spaces under conditions of shrinking as a main field of their responsibility. The situation in Germany represents the main focus of research. So far, merely several observations and descriptions of the topic 'Public space under structural change' exist. However, no scientifically proved publications are available, although till today a lot of practical planning experience mainly has been gained through the implementation of projects of temporary use and regeneration by local authorities in Eastern Germany. At the same time, projections indicate that the decrease of population and economic decline will be the determining factors of future urban development in many cities. Hence, this thesis aims to further develop an emerging research field which so far has been given only little attention. This will be done through a secondary data analysis of the existing knowledge pools and through an empirical analysis based on expert interviews. For both areas of research one can conclude that city shrinkage leads to various spatial transformations and to changes in the way municipal planning operates in this main area of interest ('public space'). The impacts are as follows: 1. quantitative growth of public space, 2. lower frequency of use, 3. modified structure of user groups, 4. declining social control, 5. strategic prioritisation of green spaces and 6. comprehensive management of public space by local stakeholders. Against this background, shrinking adds to transformations of public space that have already been observed for other urban contexts. The transformation process particularly affects the traditional characteristics of public space and the attitude of local stakeholders towards it. This is happening in a way so that according to one conclusion of this thesis key terms of urban sociology which describe, measure and explain public space no longer seem to be adequate under conditions of shrinkage. Furthermore, the production of public space will reach its limits when citizens´ and property owners´ willingness to cooperate and to contribute and external funding are no longer properly coordinated. Finally, the thesis outlines the need for further research. This particularly is required to broaden the empirical base in order to provide more representative data in the future. Furthermore, the analysis of knowledge pools and experts' interviews highlighted several issues of research, which need further investigation. These are, for example, the citizens´ behaviour, the use of public space and the cooperation between local planning authorities and the public.
Public space under conditions of shrinking.
Keywords: Stadtplanung; Öffentlicher Raum; Schrumpfung; Wohnungsmarkt; Bevölkerungsentwicklung; Gemeindefinanzen; Freiraumgestaltung; Flächennutzung; Stadtsoziologie; Befragung; Kooperation; Bewohnerbeteiligung; Wohnumfeld; Stadtumbau; Akteur; Fallbeispiel; Zwischennutzung